Implementasi Konsep Ekuitas Merek Di Indonesia: Sebuah Perspektif Keuangan - Wardianto, K. Bagus (Business UHO: Jurnal Administrasi Bisnis, 2019)
The brand is a very important asset in winning business competition. Banks with high brand equity will find it easy to get customers to save and borrow funds in the bank. The purpose of this study is to describe brand equity using a financial perspective, because this research is a descriptive study. This research was conducted at a state-owned commercial bank with an observation period of 2010 to 2015. The method used to calculate brand value is the Hirose method, so data is needed since four years before the base year. The data analyzed in this study are secondary data from 2006 to 2015 collected through the documentation of state-owned commercial bank financial statements published on the Indonesia Stock Exchange. The findings from the study note that in general state-owned commercial banks experienced an increase in brand value during the observation period 2010 to 2015. Based on the concept of resource-based view, state-owned commercial banks can optimize their brand equity as intangible assets to improve company performance. Based on the signaling theory, it is known that state-owned banks are in good condition because in general they have increased from 2010 to 2015.